Ectopic adrenocortical adenoma in liver disguising as hepatocellular carcinoma: A case report and literature review - Jixuan Duan; Chong Peng; Ting Sun; Heng Wen; Fangyan Lu; Yan Zheng; Wenjin Zhang (Human Pathology Reports, 2025)
Due to the anatomical proximity between the right adrenal gland and the liver, hepatic ectopic adrenocortical adenomas (HEAA) are frequently misdiagnosed as hepatocellular carcinoma (HCC), primarily because of their similar imaging characteristics. In this report, we present a case of HEAA that was initially misdiagnosed as HCC despite comprehensive preoperative evaluation. The review of the literature indicated HEAA showed no gender predilection. The imaging characteristics on both computed tomography (CT) and MRI frequently overlapped with those of HCC. Immunohistochemistry(IHC) proved essential for accurate differential diagnosis. Through comprehensive evaluation of all reported cases, we identified Melan-A and inhibin-α as particularly specific markers for HEAA. The accurate diagnosis of HEAA presents significant challenges, with frequent misdiagnosis as other hepatic tumors. Our analysis of this case and 10 comparable cases demonstrates that IHC serves as the cornerstone for distinguishing HEAA from HCC.